A strategy for refining the calculation of contacts in protein-RNA complexes - Bastos, Luana Luiza; Lemos, Rafael P.; Mariano, Diego; Melo-Minardi, Raquel C. de (Anais do Simpósio Brasileiro de Bioinformática (BSB), 2024)
Protein-RNA interactions are essential for several biological processes, including gene expression. However, traditional methods for studying these interactions use superficial criteria to perform this analysis, which can lead to false positives. This study presents a new strategy for modeling protein-RNA contacts. We classify RNA atoms and integrate methods previously used for protein contacts, developing the proposed approach that detects a broader range of interactions. We compare our proposal to an existing benchmark and observe that this method identifies more contacts and provides detailed insights into different types of interactions, such as aromatic stacking and hydrogen bonding. We envision that the strategy could improve the development of protein-RNA interaction databases and deepen our understanding of these complexes.